The kid's calendar : 1994 - Lester, Alison (St. Leonards, N.S.W. : Allen & Unwin, 1993)
"Pictures that show kids doing their favourite things all through the Australian year" -- Back cover.
For children.
Keywords: Art calendars -- Juvenile literature; Calendars -- Australia -- Juvenile literature